Evaluation of Portuguese community health projects and initiatives within the European and national healthy cities network - Rito,Ana Isabel (2019)
Introduction: Following the World Health Organization European Healthy Cities Network, the Portuguese Healthy Cities Network was formally created by municipalities equally committed to promote equity, health and quality of life through local action. Objectives: To evaluate the health promotion strategies and initiatives implemented at municipality level in the Portuguese Healthy Cities Network and to confirm if these were in line with the requirements of the Health 2020 policy integrated on Phase VI of European Healthy Cities Network (2014-2018). Methodology: An exploratory-descriptive methodological design was used and a semi-structured questionnaire, developed by the World Health Organization Regional Office for Europe, was applied to the 29 municipalities of the Portuguese Healthy Cities Network (2013) invited to participate. 22 (75.8%) healthy cities met the criteria and were included. Results: Programmes on promotion of physical activity were the most frequently implemented across the Portuguese Healthy Cities Network (81.8%). All municipalities (100%) reported that children (>5 years) were the main targeted group of Portuguese Healthy Cities Network initiatives, followed by elderly (95.5%), adolescents (86.4%) and adults (86.4%). Low levels (27% - 32%) of initiatives that engaged other stakeholders, were reported as well as there was lack of research projects related to health matters and established partnerships by the scientific community. Overall, there was a perception of a positive impact of the Portuguese Healthy Cities Network programmes as 50% of the municipalities reported a remarkable improvement in health and quality of life of the population. Conclusions: Although life-course initiatives addressing the major burden of diseases were implemented, a more comprehensive approach is needed to follow Health 2020 principles. Development and reinforcement of the Portuguese Healthy Cities Network programmes is still a challenge. It should cover different population groups in order to tackle social inequalities and it also demands new partnerships, new forms of communication, as well as monitoring and evaluation mechanisms in place.